The Relationship Between Image, Personal Relationship and Hotel's Customer Loyalty in Jakarta - Riorini, Sri Vandayuli (Business and Entrepreneurial Review, 2006)
Consumer's loyalty is one of the important factors to achieve success for an organization. For service industry, image of service provider is crucial in order to create consumer's loyalty. Moreover, personal relationship between the company staff and consumers becomes very important to build the loyalty of service consumers, however, this relationship is less important for the tangible products.The purpose of this research is to analyze the relationship between imageand personal relationship with the loyalty of hotel consumers in Jakarta, The Result of this research has significant implications for service providers, especially hotels. Initially, this research indicates the importance of image and personal relationship to determine consumer loyalty which can be used as a reference for hotel managers to improve the hotel's service standard. Second, this research indicates significant proof in understanding hotel guests' behaviour that loyal consumers will tend to repurchase. Management or provision of service and interaction between hotel guests and improper staff behaviour will result in consumers' disloyalty and may cause consumers to move to competitors.